2010
DOI: 10.1038/clpt.2010.158
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Drug Interaction Potential of Pazopanib, an Oral Vascular Endothelial Growth Factor Receptor Tyrosine Kinase Inhibitor, Using a Modified Cooperstown 5+1 Cocktail in Patients With Advanced Solid Tumors

Abstract: Pazopanib, an oral inhibitor of vascular endothelial growth factor receptor, platelet-derived growth factor receptor, and c-kit kinases, inhibits multiple cytochrome P450 (CYP450) enzymes in vitro. This study in patients with advanced cancer evaluated the effect of pazopanib on CYP450 function by comparing the pharmacokinetics of CYP-specific probe drugs in the presence and absence of pazopanib. The probes used included midazolam (CYP3A specific), warfarin (CYP2C9 specific), omeprazole (CYP2C19 specific), caff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 17 publications
2
61
0
Order By: Relevance
“…To identify these mean exposure levels in the absence of pharmacokinetic data, we fitted an E max model to mean AUC values reported in previous clinical trials; this approach enabled us to account for the less‐than‐dose‐proportional increase in AUC. Data from five clinical trials that investigated pazopanib doses of 5 mg to 2,000 mg administered once daily were pooled for the analysis 28, 29, 30, 31, 32. According to the E max model, mean exposure was 771.6 μg·h/mL (range, 629.4–802.4 μg·h/mL) corresponding to a mean dose of 727 mg (range: 473–800 mg) through the population of 47 patients.…”
Section: Resultsmentioning
confidence: 99%
“…To identify these mean exposure levels in the absence of pharmacokinetic data, we fitted an E max model to mean AUC values reported in previous clinical trials; this approach enabled us to account for the less‐than‐dose‐proportional increase in AUC. Data from five clinical trials that investigated pazopanib doses of 5 mg to 2,000 mg administered once daily were pooled for the analysis 28, 29, 30, 31, 32. According to the E max model, mean exposure was 771.6 μg·h/mL (range, 629.4–802.4 μg·h/mL) corresponding to a mean dose of 727 mg (range: 473–800 mg) through the population of 47 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Though in vitro data suggests that pazopanib inhibits many CYP enzymes, a pharmacokinetic study using CYP-specifi c probe drugs demonstrated that pazopanib is a weak inhibitor of CYP3A4 and CYP2D6 with no effect on CYP1A2, CYP2C9, or CYP2C19 (Goh et al 2010 ). Of interest in the palliative care setting, the CYP3A4-specifi c probe that was utilized was midazolam, suggesting that pazopanib has the potential to decrease the clearance of midazolam.…”
Section: Vegf Tkismentioning
confidence: 98%
“…It is not clear that gefitinib alters the elimination of warfarin since it did not inhibit these CYP. Pazopanib (800 mg once daily) did not modify S-warfarin pharmacokinetics in 19 cancer patients underlining the lack of clinical impact on CYP2C9-mediated metabolism [96], in opposition with CYP2C9 inhibition reported in liver microsomes.…”
Section: Effects Of Kinase Inhibitors On the Pharmacokinetics Of Co-amentioning
confidence: 98%
“…Pazopanib slightly (35%) increased midazolam (CYP3A probe given orally) plasma concentrations indicating that it is a weak CYP3A inhibitor. In addition, pazopanib was found to inhibit CYP2D6 (33-64%) when assessed by the dextromethorphan/dextrorphan urine concentration ratio [96].…”
Section: Effects Of Kinase Inhibitors On the Pharmacokinetics Of Co-amentioning
confidence: 99%